(untitled) (Research, Society and Development, 2020)
Ultrasonic tips and anatomic finishing files have been used as strategies to improve the cleaning and disinfection of root canals, especially in complex anatomies. These instruments are also subjected to fractures, which can hinder the endodontic treatment and negatively affect the outcome. This article presents two cases of successful management of intracanal-fractured instruments with unfavourable prognosis, emphasizing on treatment protocols and outcomes. Two 14-year-old female patients underwent root canal treatment of teeth 37 (case 1) and 47 (case 2). During the final irrigation protocols, case 1 presented a fractured XP-Clean file within the mesiobuccal canal and within the distal canal in case 2, which also showed fractured E1-Irrisonic tips within the mesiobuccal and distal canals. Non-surgical management and bypassing retained instrument fragments were successful in both cases and they may be considered adequate approaches.